The future market for the flowers of Pyrethrum - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Chrysanthemum cinerariaefolium, used for the production of effective, environment-friendly biopesticides could be under pressure. Pyrethrum was first introduced to Kenya in 1928 and production has been increasing steadily in recent years. In 1991...